Genetic liability to asthma and risk of cardiovascular diseases: A Mendelian randomization study - Chen, Heng; Chen, Wei; Zheng, Liangrong (Frontiers in Genetics, 2022)
Background and Aims: Epidemiological studies have suggested positive associations between asthma and the risk of cardiovascular diseases (CVDs). However, causality remains inconclusive. We aim to explore the causal associations between asthma and CVDs risk using the Mendelian Randomization (MR) approach. Methods: We obtained summary-level data for 8 CVDs [including atrial fibrillation (AF), coronary artery disease (CAD), heart failure (HF), stroke, ischemic stroke, large artery stroke, small vessel stroke, and cardioembolic stroke] from several large genome-wide association studies (GWASs) and the FinnGen consortium. Nine lead single-nucleotide polymorphisms associated with asthma (P < 5 × 10-8) were identified from the GWAS conducted by the Trans-National Asthma Genetic Consortium. MR analyses were performed using the inverse variance weighted method, supplemented by the weighted median and MR-Egger methods. Results: Inverse variance weighted method showed suggestive effects of genetically determined asthma on AF (odds ratio (OR), 1.08; 95% confidence interval (CI), 1.02, 1.14; P = 0.009) and HF (OR, 1.05; 95% CI, 1.01, 1.09; P = 0.029). We found no causal associations between asthma and other CVDs. No horizontal pleiotropy was observed. Conclusion: This MR study provides genetic evidence suggesting a causal association between asthma and the risk of AF and HF, although not at the level of significance after multiple testing correction. Programs aimed at treating asthma among asthmatics might help prevent the adverse health effects inflicted by CVDs.